The relative reinforcing efficacy of nicotine in an adolescent rat model of attention-deficit hyperactivity disorder - Smethells, John R.; Burroughs, Danielle; Saykao, Amy; LeSage, Mark G. (Frontiers in Psychiatry, 2023)
Attention-deficit/hyperactivity disorder (ADHD) is an independent risk factor for tobacco use disorder. Individuals with ADHD are more likely to begin smoking at a younger age, become a daily smoker sooner, smoke more cigarettes per day, and exhibit greater nicotine dependence than individuals without ADHD. It is unclear whether these findings are due to the reinforcing efficacy of nicotine per se being greater among individuals with ADHD. The purpose of the present study was to examine this issue using an animal model of ADHD, the spontaneously hypertensive rat (SHR) strain. Adolescent SHR and Wistar (control) rats were given access to a typically reinforcing nicotine unit dose (30 µg/kg), a threshold-reinforcing nicotine dose (4 µg/kg), or saline under an FR 1 (week 1) and FR 2 (week 2) schedule during 23 hr sessions to examine acquisition of self-administration. Behavioral economic demand elasticity was then evaluated at the 30 µg/kg dose through an FR escalation procedure. At the 30 µg/kg dose, SHR rats exhibited a lower average response rate, lower mean active to inactive lever discrimination ratio, and lower proportion of rats acquiring self-administration compared to control rats. During demand assessment, SHR rats showed no significant difference from Wistars in demand intensity (Q0) or elasticity (; i.e., reinforcing efficacy). In addition, no strain difference in acquisition measures were observed at the 4 µg/kg dose. These findings suggest that the increased risk of tobacco use disorder in adolescents with ADHD may not be attributable to a greater reinforcing efficacy of nicotine, and that other aspects of tobacco smoking (e.g., non-nicotine constituents, sensory factors) may play a more important role. A policy implication of these findings is that a nicotine standard to reduce initiation of tobacco use among adolescents in the general population may also be effective among those with ADHD.